8y-(3y+6)=14

Simple and best practice solution for 8y-(3y+6)=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8y-(3y+6)=14 equation:


Simplifying
8y + -1(3y + 6) = 14

Reorder the terms:
8y + -1(6 + 3y) = 14
8y + (6 * -1 + 3y * -1) = 14
8y + (-6 + -3y) = 14

Reorder the terms:
-6 + 8y + -3y = 14

Combine like terms: 8y + -3y = 5y
-6 + 5y = 14

Solving
-6 + 5y = 14

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 5y = 14 + 6

Combine like terms: -6 + 6 = 0
0 + 5y = 14 + 6
5y = 14 + 6

Combine like terms: 14 + 6 = 20
5y = 20

Divide each side by '5'.
y = 4

Simplifying
y = 4

See similar equations:

| q+-3r=2 | | 24=-4k | | 13r+42=81 | | 259+14h=22h | | -27=-8+p | | 5-(-4)c=2c+2c+3 | | 4+2(3x+9)=28 | | -12=n/17 | | 1=-1r-15 | | n/9=14 | | 6z=4(1.5z-8) | | -13p=52 | | 7x-30=4x+60 | | 6(x+4)=7x+16 | | -5x-2x=42 | | 3x=8-3(x+4) | | -2y-2z+10+2y-z=8 | | 15-(12x+3)/-3=-6 | | 6c+4c+20c+-19c+-6=-20 | | p^2+12+4=0 | | -3(6v-3)+5v=3(v+5) | | 5m+13+6m=m-37 | | 7(x+3)=112 | | -(r-1)+r=2r-3(r+5) | | -8/3/8/3 | | 18+10g+4g=11 | | -2(x+8)-2(x+4)=2x+2x | | 35=-5/9w | | 585.00+0.13x=850.00 | | 6(k+5)-(3+7k)=24 | | -(6+5n)-8(1-n)=3n-4 | | 14x^4-4x^3+8x^2= |

Equations solver categories